The Clinical Challenges of Diagnosing Acutely Decompensating Amyloidosis - Bayanzay, Karim (Cureus, 2020)
Advanced amyloidosis and related multi-organ manifestations are devastating clinical scenarios. Because ambiguous presentation of amyloidosis may occur, early diagnosis and prevention of organ damage, such as cardiac injury, is essential and requires high clinical intuition. Our patient was a middle-aged female with a past medical history of heart failure with several decompensation episodes who presented with jaundice, itchiness, and weight loss. Further workup revealed pulmonary hypertension, restrictive heart disease, possible underlying obstructive liver disorder, and hyperkalemia. During admission, the patient established bradycardia and required a pacemaker temporarily, and later she manifested atrial fibrillation. Liver biopsy primarily was suggestive of hepatic congestion. Unfortunately, the patient died during workup due to cardiac arrest. Premortem laboratory results were suggestive of amyloidosis, which was confirmed later by re-examining the liver biopsy with Congo red. Diagnosis of amyloidosis requires early clinical suspicion and workup to prevent its progression to fatal organ involvement such as cardiac complications.